682Do job stressor—mental health relationships vary by migrant status? An Australian comparative analysis. (2nd September 2021) - Liu, Xiaomin; LaMontagne, Anthony; Bowe, Steven; Li, Lin; Too, Lay San
Abstract: Background: Migrants may be more likely to experience occupational health inequities (OHIs) than native-born workers due to higher occupational exposure, higher vulnerability to exposure-associated health impacts, or both. This study explores migrant status-related differences in vulnerability to job stressor exposures in terms of mental health in Australia. Methods: Data were from wave 14 of the Household Income and Labour Dynamics in Australia Survey. Migrant status was defined by country of birth (COB), the dominant language of COB, and the years since arrival in Australia. Job stressors included skill discretion, decision authority, and job insecurity. Mental health was assessed using the Mental Health Inventory-5 score (MHI-5). Data were analysed using linear regression, adjusting for gender, age, and education. Migrant status was analysed as the effect modifier of job stressor—mental health relationships. Results: As expected, skill discretion and decision authority were positively, while job insecurity was negatively associated with the MHI-5 score. However, there was no statistical evidence of migrant status acting as an effect modifier of job stressor—mental health relationships even though the dominant language of COB and years since arrival in Australia have been taken into account. Conclusions: The magnitudes of job stressor—mental health relationships do not differ between migrant workers and Australia-born workers. Key messages: Differential exposure rather than differential vulnerability is a more important mechanism for generating occupational mental health inequities between migrants and Australian-born workers. Reducing job stressor exposures could reduce the OHIs among migrant workers in Australia.